Strong MARSIS Radar Reflections From the Base of Martian South Polar Cap May Be Due to Conductive Ice or Minerals. Issue 13 (6th July 2021) - Bierson, C. J.; Tulaczyk, S.; Courville, S. W.; Putzig, N. E.
Abstract: Recent results from the Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) instrument have been interpreted as evidence of subsurface brine pooled beneath 1.3 km‐thick South Polar Layered Deposit (SPLD). This interpretation is based on the assumption that the regionally high strength of MARSIS radar reflections from the base of the ice cap is due to a strong contrast in dielectric permittivity across the basal interface. Here, we demonstrate that the high‐power reflections could instead be the result of a contrast in electric conductivity. While not explicitly excluding a liquid brine, our results open new potential explanations for the observed strong radar reflections, some of which do not require liquid brine beneath SPLD. Potential basal materials with suitably high conductivity include clays, metal‐bearing minerals, or saline ice. Plain Language Summary: Previous work reported a regionally strong radar reflection under Mars' south polar ice sheet. Due to its brightness, this radar reflection was interpreted as liquid water (likely with high concentration of dissolved salts). A radar reflection can be bright due to a large contrast in either dielectric permittivity or electric conductivity. Previous work only considered contrasts in dielectric permittivity. We find that contrasts in electric conductivity between materials could also explain the brightness of the reflection. We suggest that this difference could be due to clays, metal‐bearing minerals, or saline ice under the polar ice sheet. Key Points: Radar reflections can be caused by contrasts in either dielectric permittivity or electric conductivity Reflections observed by Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) at Mars' south polar region can be explained by contrasts in electric conductivity and do not require liquid water We propose that a polar‐ice substrate containing clays, other conductive minerals, or saline ice are the most plausible candidate materials